2022
DOI: 10.20517/and.2022.05
|View full text |Cite
|
Sign up to set email alerts
|

Review of evidence implicating the plasminogen activator system in blood-brain barrier dysfunction associated with Alzheimer’s disease

Abstract: Elucidating the pathogenic mechanisms of Alzheimer’s disease (AD) to identify therapeutic targets has been the focus of many decades of research. While deposition of extracellular amyloid-beta plaques and intraneuronal neurofibrillary tangles of hyperphosphorylated tau have historically been the two characteristic hallmarks of AD pathology, therapeutic strategies targeting these proteinopathies have not been successful in the clinics. Neuroinflammation has been gaining more attention as a therapeutic target be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…142,143 There are three types of NPs, including atrial natriuretic peptide (ANP), C-type natriuretic peptide (CNP) and brain natriuretic peptide (BNP). 1 NPs act on specific natriuretic peptide receptors (NPR), including NPR-A, NPR-B and NPR-C. 140,143 NPs are also expressed in the brain, mainly in neurons, glial cells and neurovascular units. 8 They improve BBB integrity, synaptic plasticity, memory function, neurotransmitter release and attenuation of neuroinflammation.…”
Section: Nep Inhibitors and Natriuretic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…142,143 There are three types of NPs, including atrial natriuretic peptide (ANP), C-type natriuretic peptide (CNP) and brain natriuretic peptide (BNP). 1 NPs act on specific natriuretic peptide receptors (NPR), including NPR-A, NPR-B and NPR-C. 140,143 NPs are also expressed in the brain, mainly in neurons, glial cells and neurovascular units. 8 They improve BBB integrity, synaptic plasticity, memory function, neurotransmitter release and attenuation of neuroinflammation.…”
Section: Nep Inhibitors and Natriuretic Peptidesmentioning
confidence: 99%
“… 138 Remarkably, hyperfibrinolysis induces BBB injury through the generation of endogenous BK 139 . Besides, the overexpression of tissue plasminogen activator (tPA) and plasmin are linked with AD development by accelerating the accumulation of Aβ 140,141 . Therefore, higher BK in AD could be related to hyperfibrinolysis and higher tPA.…”
Section: Mechanistic Role Of Nep Inhibitors In Admentioning
confidence: 99%
“…In addition to activating microglia, fibrin(ogen) can also trigger the activation of neutrophils, which release toxic ROS and neutrophil extracellular traps (NETs), leading to excessive immune activation and inflammation [ 110 ]. An additional inflammatory factor is the fibrinolytic system, converting plasminogen to fibrin-dissolving plasmin [ 111 ]. The plasminogen activator system is thought to be involved in promoting brain inflammation, plaque deposition, and BBB dysfunction in AD [ 111 ].…”
Section: Interaction Of Aß With the Plasma Contact System And Its Dri...mentioning
confidence: 99%
“…An additional inflammatory factor is the fibrinolytic system, converting plasminogen to fibrin-dissolving plasmin [ 111 ]. The plasminogen activator system is thought to be involved in promoting brain inflammation, plaque deposition, and BBB dysfunction in AD [ 111 ].…”
Section: Interaction Of Aß With the Plasma Contact System And Its Dri...mentioning
confidence: 99%
“…Cell senescence, with the classical phenotypic hallmarks include senescence-associated β-galactosidase (SA-β-gal), cell cycle arrest, persistent DNA damage response (DDR), and senescenceassociated secretory phenotype (SASP) including inflammatory cytokines, growth factor, matrix metalloproteinases, and other proteinases (Coppé et al, 2010;Cuollo et al, 2020;Fafián-Labora and O'Loghlen, 2020), has been demonstrated to play an important role in onset and aggravation of AD (Martínez-Cué and Rueda, 2020). Recent studies have shown that plasminogen activator inhibitor-1 (PAI-1) also presents a key marker of cell senescence and contributes to various aging-associated morbidities (Gerenu et al, 2017;Vaughan et al, 2017;Kritsilis et al, 2018;Bryant et al, 2020;Tang et al, 2022). Mounting evidence has demonstrated that diseaseassociated microglia display several features of senescence and preventing microglia from senescence could lead to reduced amyloidosis and synaptic damage in age-related AD (Daria et al, 2017;Hu et al, 2021;Hu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%